Análise numérica da propagação de incêndio entre edificações confrontes - Guimarães, Sane Alves (2022)
Fire safety aims to preserve life and property. One of the passive measures against fire is the building distance that seeks to avoid the protection against fire protection, protected by a fire protection. There is no unified determination to determine this distance and, in Brazil, it is the responsibility of the federated states to issue norms or technical instructions that address this issue. Such percentage norms and instructions adopt simplifications, as is the case of the consideration of openings in the facades, which do not take into account the format and distribution of the openings, but only theirs in relation to the total area of the compartment. However, fire environments are complex and as contemporary buildings present more and more differentiated spaces and spaces. Thus, dissertation, as an analysis of numerical simulations in the Fire Dynamics Simulator (FDS) computer program, this fire research aims to build openings in the facades, one of these openings and the occupation of the building. The higher results indicate that opening rates lead to higher temperatures inside the burned building and on the facade of the confronted building. The openings with a lower rate made it difficult for smoke to escape and limited the supply of oxygen. As for the distribution of the facades, the models with distribution in the vicinity of temperatures lower than the uniform distribution. In general, the concentration of the openings made it difficult for smoke to escape and the entry of oxygen was not uniform along the entrance. Regarding the types of occupations, that is, the fire load, the higher the fire load, the higher the temperature and heat flow in the confrontation. Finally, the influence of distance for great fire protection was perceived from safety and the same measure should be treated in an ideal way such a measure for fire protection. In addition, as per safe standards, renovations that enable fire protection protection, and for safety, allow changes and upgrades to occur.